PENGARUH KOMBINASI MIKORIZA+MHB DENGAN PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Vivi Meila Setyawanda; Imam Mudakir; Iis Nur Asyiah (Saintifika, 2016)
Abstract: Giving mycorrhiza + MHB with goat manure to cocoa seeds to increase cocoa growth. The purpose of this study was to examine the effect of mycorrhiza + MHB combination with goat manure on cocoa seed growth (Theobroma cacao L.). This research used Factorial Randomized Complete Random Design (RAL) with two factors ie first factor of mycorrhizal + MHB with three levels of 0 g (m0), 7.5 g (m1), and 12.5 g (m2), the second factor goat manure with three taragos 0 g (k0), 100 g (k1), and 200 g (m2), and combination factors m0k0, m0k1, m0k2, m1k1, m1k2, m2k2, m2k0, m2k1, and m2k2 . The data obtained were analyzed using Anova and Duncan's advanced test. From the results of this study can be concluded that giving mycorrhiza + MHB with goat manure significantly influence the growth of cocoa seedlings (Theobroma cacao L.). Treatment with 7.5 g of mycorrhiza + MHB with 200 g of goat manure showed the best results on the growth of cocoa seeds compared with other treatments Keywords: Cocoa; Mycorrhiza + MHB; Growth; Goat Cage Manur.